Dengue human infection models to advance dengue vaccine development - Larsen, Christian P.; Whitehead, Stephen S.; Durbin, Anna P. (Vaccine, 2015)
•Neutralizing antibody did not correlate with efficacy in trials of the lead vaccine candidate CYD™.•Partial immunity to dengue may predispose to more severe disease.•Animal models do not replicate the characteristics of dengue infection seen in humans.•Dengue human infection models can advance dengue vaccine development. Dengue viruses (DENV) currently infect approximately 400 million people each year causing millions to seek care and overwhelming the health care infrastructure in endemic areas. Vaccines to prevent dengue and therapeutics to treat dengue are not currently available. The efficacy of the most advanced candidate vaccine against symptomatic dengue in general and DENV-2 in particular was much lower than expected, despite the ability of the vaccine to induce neutralizing antibody against all four DENV serotypes. Because seroconversion to the DENV serotypes following vaccination was thought to be indicative of induced protection, these results have made it more difficult to assess which candidate vaccines should or should not be evaluated in large studies in endemic areas. A dengue human infection model (DHIM) could be extremely valuable to down-select candidate vaccines or therapeutics prior to engaging in efficacy trials in endemic areas. Two DHIM have been developed to assess the efficacy of live attenuated tetravalent (LATV) dengue vaccines. The first model, developed by the Laboratory of Infectious Diseases at the U. S. National Institutes of Health, utilizes a modified DENV-2 strain DEN2Δ30. This virus was derived from the DENV-2 Tonga/74 that caused only very mild clinical infection during the outbreak from which it was recovered. DEN2Δ30 induced viremia in 100%, rash in 80%, and neutropenia in 27% of the 30 subjects to whom it was given. The Walter Reed Army Institute of Research (WRAIR) is developing a DHIM the goal of which is to identify DENV that cause symptomatic dengue fever. WRAIR has evaluated seven viruses and has identified two that meet dengue fever criteria. Both of these models may be very useful in the evaluation and down-selection of candidate dengue vaccines and therapeutics.